Adipose Tissue‐Derived Mesenchymal Stem Cells Improve Revascularization Outcomes to Restore Renal Function in Swine Atherosclerotic Renal Artery Stenosis123. (9th April 2012) - Eirin, Alfonso; Zhu, Xiang‐Yang; Krier, James D.; Tang, Hui; Jordan, Kyra L.; Grande, Joseph P.; Lerman, Amir; Textor, Stephen C.; Lerman, Lilach O.
Abstract: Reno‐protective strategies are needed to improve renal outcomes in patients with atherosclerotic renal artery stenosis (ARAS). Adipose tissue‐derived mesenchymal stem cells (MSCs) can promote renal regeneration, but their potential for attenuating cellular injury and restoring kidney repair in ARAS has not been explored. We hypothesized that replenishment of MSC as an adjunct to percutaneous transluminal renal angioplasty (PTRA) would restore renal cellular integrity and improve renal function in ARAS pigs. Four groups of pigs ( n = 7 each) were studied after 16 weeks of ARAS, ARAS 4 weeks after PTRA and stenting with or without adjunct intrarenal delivery of MSC (10 × 10 6 cells), and controls. Stenotic kidney blood flow (renal blood flow [RBF]) and glomerular filtration rate (GFR) were measured using multidetector computer tomography (CT). Renal microvascular architecture (micro‐CT), fibrosis, inflammation, and oxidative stress were evaluated ex vivo. Four weeks after successful PTRA, mean arterial pressure fell to a similar level in all revascularized groups. Stenotic kidney GFR and RBF remained decreased in ARAS ( p = .01 and p = .02) and ARAS + PTRA ( p = .02 and p = .03) compared with normal but rose to normal levels in ARAS + PTRA + MSC ( p = .34 and p = .46 vs. normal). Interstitial fibrosis, inflammation, microvascular rarefaction, and oxidative stress were attenuated only in PTRA + MSC‐treated pigs. A single intrarenal delivery of MSC in conjunction with renal revascularization restored renal hemodynamics and function and decreased inflammation, apoptosis, oxidative stress, microvascular loss, and fibrosis. This study suggests a unique and novel therapeutic potential for MSC in restoring renal function when combined with PTRA in chronic experimental renovascular disease. STEM CELLS 2012;30:1030–1041